Security of energy supply in the European Union measured by REES and CERE indices - Dudek, Pavel (2014)
This thesis tries to summarize current situation in the European Union from the perspective of security of energy supply. In the first part I summarize development of security of energy supply legislation in the European Union, in the second part I compare different methods used to measure security of energy supply and in the third part I use two indices CERE and REES (Contribution to EU risk exposure, Risky External Energy Supply) and measure risk exposure and its development for particular countries between years 2006 and 2012.